Systematic Literature Review (SLR) Peran Asuransi Syariah dalam Membantu Perkembangan UMKM di Masa Pandemi - Ashif Jauhar Winarto (STAI Nurul Islam Mojokerto, 2022)
This study aims to describe the role of Islamic insurance in helping the development of MSMEs during a pandemic. which sharia insurance has two contracts, namely tijarah and tabarru'. As an effort to help the development of MSMEs, sharia insurance has a new breakthrough, namely by going to Tabbaru' to help each other between MSMEs and insurance parties. And the profits that will be shared are because it is done by the insurance, namely investments with investments that use sharia principles. In sharia insurance there will be tijarah which also provides benefits to MSMEs during a pandemic, as well as in sharia insurance there is already a halal guarantee by the Indonesian Ulema Council or MUI through the DSN fatwa (National Sharia Council with Fatwa No. 21/DSN-MUI/X/2001 concerning general guidelines for sharia insurance.The method used in this research is the Systematic Literature Review (SLR) method by Bettany-Saltiknov (2012) by summarizing the findings from previous studies that are relevant to the research topic.So the topics that are deemed relevant to this research are will be discussed, criticized and concluded.